2015
DOI: 10.3892/or.2015.3876
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combination chemotherapy using a novel oral chemotherapeutic agent, TAS-102, together with bevacizumab, cetuximab, or panitumumab on human colorectal cancer xenografts

Abstract: TAS-102 is a novel oral nucleoside antitumor agent that consists of trifluridine (FTD) and tipiracil hydrochloride (TPI) at a molecular ratio of 1:0.5, and was approved in Japan in March 2014 for the treatment of patients with unresectable advanced or recurrent colorectal cancer that is refractory to standard therapies. In the present study, we used colorectal cancer xenografts to assess whether the efficacy of TAS-102 could be improved by combining it with bevacizumab, cetuximab or panitumumab. TAS-102 was or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 28 publications
1
85
0
1
Order By: Relevance
“…In two preclinical trials, the antitumor efficacy was significantly enhanced. The concentrations of FTD and FTD phosphates were obviously higher in combination treatment of bevacizumab and TAS-102 than either monotherapy on human CRC xenografts 28,29. Soon after, in order to assess effectiveness and security, an open-label, single-arm, multicenter Phase I/II study (C-TASK FORCE) was performed 30.…”
Section: Discussionmentioning
confidence: 99%
“…In two preclinical trials, the antitumor efficacy was significantly enhanced. The concentrations of FTD and FTD phosphates were obviously higher in combination treatment of bevacizumab and TAS-102 than either monotherapy on human CRC xenografts 28,29. Soon after, in order to assess effectiveness and security, an open-label, single-arm, multicenter Phase I/II study (C-TASK FORCE) was performed 30.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have recognized several effective combinations in vitro and in vivo, including combinations with oxaliplatin, irinotecan, cetuximab, and bevacizumab. [93][94][95] The first phase 1 study assessing the recommended dose and safety of TAS-102 in combination with irinotecan has been completed, but due to a limited sample size, no conclusions could be drawn. [96] A Japanese phase 1/2 study investigating TAS-102 in combination with bevacizumab showed a PFS rate of 42.9% at 16 weeks and an acceptable toxicity profile, with a recommended TAS-102 dose of 35 mg/m 2 twice daily on days 1-5 during weeks 1 and 2, followed by 2 weeks of rest with bevacizumab 5 mg/kg every 2 weeks.…”
Section: Combination Treatmentmentioning
confidence: 99%
“…TFTD in combination with irinotecan hydrochloride (18), oxaliplatin (19), bevacizumab, cetuximab, or panitumumab (20) exhibited superior in vivo activity against human colorectal cancer, including 5-FU-resistant tumors, compared with any of these drugs alone, as demonstrated by previous studies. In the present study, the effects of TFTD in combination with nintedanib against human colorectal tumor xenografts in a nude mouse model were evaluated.…”
Section: Introductionmentioning
confidence: 54%